2018
DOI: 10.5194/piahs-377-35-2018
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of sediment deposits in the Ghézala reservoir in northern Tunisia

Abstract: Abstract. The control of sedimentation in a reservoir provides a global evaluation of the process of erosion and transportation of sediment. Knowledge of sedimentation is useful for reservoir management. Bathymetric surveys can be used to assess the silting volume of dams. The results of two surveys of the Ghézala dam reservoir in northern Tunisia are available. The measurements provide initial information about the quantity and variability of silting and the mechanism of sediment deposition. According to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Tolessa et al (2019) demonstrated that the expansion of cultivated land to the detriment of natural vegetation is significantly affecting the natural resources. Also, Mathlouthi and Lebdi (2018) have reported that the pressure exerted on the soil by ploughing as well as overgrazing to meet the needs of the population of a specific watershed in Tunisia has led to the continued soil deterioration manifested by increased erosion and sedimentation in the reservoirs. In fact, agricultural and silvopastoral lands in Tunisia have undergone important changes, since the beginning of the 20 th century.…”
Section: Discussionmentioning
confidence: 99%
“…Tolessa et al (2019) demonstrated that the expansion of cultivated land to the detriment of natural vegetation is significantly affecting the natural resources. Also, Mathlouthi and Lebdi (2018) have reported that the pressure exerted on the soil by ploughing as well as overgrazing to meet the needs of the population of a specific watershed in Tunisia has led to the continued soil deterioration manifested by increased erosion and sedimentation in the reservoirs. In fact, agricultural and silvopastoral lands in Tunisia have undergone important changes, since the beginning of the 20 th century.…”
Section: Discussionmentioning
confidence: 99%